Estimating the benefits of vehicle-to-home in islands: The case of the Canary Islands. (1st September 2017) - Colmenar-Santos, A.; de Palacio-Rodriguez, Carlos; Rosales-Asensio, Enrique; Borge-Diez, David
Abstract: This paper presents a cost-benefit analysis for the bi-directional functionality of plug-in electric vehicle charging, often called vehicle-to-grid. Plug-in electric vehicles represent an opportunity to reduce emissions from transportation, improve the efficiency, and also, it is a solution for storing electricity from the grid. The research is focused on the vehicle-to-home application for plug-in electric vehicles, which entails a bi-directional energy flowing from vehicles to households. The benefits from this use of the plug-in electric vehicles batteries are peak-shaving as well as valley-filling on the load curve, resulting in cost reductions for the user and the electric power system. In the case of islands, the use of this storage would allow an increased penetration of renewable energy sources and a reduction of costs. The research discusses the impact of vehicle-to-grid for the Canary Islands, where a plug-in electric vehicles penetration charging higher than a 20% would cause changes to the current demand curve peaks. The results show the benefits to both the system operator and the users, which may reduce mobility energy costs by a 50% through the time of usage. Vehicle-to-home regulation based on standards is recommended for incentivizing its functionality, the time of usage pricing, based on market prices, being the most beneficial for the user and the electric power system as a whole. Graphical abstract: Highlights: The effects and benefits of Vehicle-to-home in islands are reviewed. The research shows Plug-in Electric Vehicles penetration above 20% changes load curve peaks. Energy costs for mobility can be reduced more than 50%. Vehicle-to-home benefit-to-cost ratio is best above seven kilowatt-hours non-transport electric consumption. Time of usage pricing proves the most beneficial mechanism for Vehicle-to-Home.